2009
DOI: 10.5210/fm.v14i5.2498
|View full text |Cite
|
Sign up to set email alerts
|

Facebook and academic performance: Reconciling a media sensation with data

Abstract: A recent draft manuscript suggested that Facebook use might be related to lower academic achievement in college and graduate school (Karpinski, 2009). The report quickly became a media sensation and was picked up by hundreds of news outlets in a matter of days. However, the results were based on correlational data in a draft manuscript that had not been published, or even considered for publication. This paper attempts to replicate the results reported in the press release using three data sets: one with a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
3
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(138 citation statements)
references
References 0 publications
2
127
3
6
Order By: Relevance
“…A much publicized report by Karpinski (2009) seems to suggest a relationship between the use of Facebook and low grades. However, a more systematic research by Pasek, More and Hargittai (2009) found the opposite to be true; that higher-grade students use Facebook more compared to the lower-grade students. They reported that Facebook use does not seem to be an indicator of academic performance.…”
Section: Uses For Informal Learningmentioning
confidence: 97%
“…A much publicized report by Karpinski (2009) seems to suggest a relationship between the use of Facebook and low grades. However, a more systematic research by Pasek, More and Hargittai (2009) found the opposite to be true; that higher-grade students use Facebook more compared to the lower-grade students. They reported that Facebook use does not seem to be an indicator of academic performance.…”
Section: Uses For Informal Learningmentioning
confidence: 97%
“…Hurt, Moss, Larson, and Lovelace (2012) compared students perception, attitudes, and educational outcomes using Facebook and conventional LMS, and showed that student group using Facebook reported better educational outcomes than the LMS group (Hurt et al, 2012). On the other hand, other authors found there was no relation between Facebook use and student success in learning (Pasek, More, & Hargittai, 2009), that there are no differences in GPA between students who did and did not use Facebook (Kolek & Saunders, 2008), and that even Facebook users can report a lower grade point average (GPA) (Kirschner & Karpinski, 2010). Junco (2012a) in his study showed that students spend significant amount of time on social networks, checking and engaging in variety of activities (Junco, 2012a), but concluded that time spent on the Facebook is a negative predictor on the GPA (Junco, 2012b).…”
Section: Introductionmentioning
confidence: 98%
“…Many studies have reported lower GPA and academic performance in students who use social networks for longer time 10,13,14 . Other studies; however, reported positive effect 10,15 or no relationship 13, [16][17][18][19] between social networks use and students grades. The variability of findings of these studies could be attributed to the different measures applied to assess social networks use or students grades.…”
mentioning
confidence: 99%